Breaking Down Silos Across Infrastructures To Improve The Visibility Of African Research Outputs - Oaiya, Omo (My University, 2023)
This presentation was delivered at Open Repositories 2023 Conference as part of Panel 7: LIBSENSE Africa - Breaking down silos across infrastructures to improve the visibility of African research outputs.
Keywords: African Research Outputs; Visibility; Infrastructure